Evaluation with Acoustic Rhinometry of patients undergoing sinonasal surgery - Raja Lope Ahmad, Raja Ahmad Al'konee; Balwant Singh, Gendeh (Malaysian Medical Associations, 2003)
The purpose of this study is to evaluate the use of Acoustic Rhinometry in assessing surgical outcomes in sinonasal surgery. This prospective study was carried out from January till december 2001. A group of 44 patients who presented with nasal obstruction due to various rhinologic abnormality were examined with acoustic rhinometry pre and post-operatively. They also were examined with acoustic rhinometry pre and post decongestion with cocaine and adrenaline. A highly significant correlation existed between minimal cross sectional area ( MCA ) and the subjective feeling of nasal problem, pre and post surgery. Thus MCA is a valuable parameter to express objectively the nasal patency. The mucovascular component of the nasal cavity plays a major role in the nasal patency as determined in the pre and post-decongestion acoustic rhinometry measurement. Acoustic rhinometry is a good tool to evaluate the nasal patency in cases where sinonasal surgery is considered in correcting the abnormality as well as for the post-operative evaluation.